MYSTERY AND THE POSTMODERN SCENE: PYNCHONEAN VIEW - Halim, Amira (Journal of Human Sciences, 2016)
In the postmodern scene, there exists a range of views that make this period different from earlier ones. This article presents a descriptive depictionof the postmodern concept of mystery presented by the postmodernists and Thomas Pynchon as to portray a dramatic scene of the two main participants in an enigmatic conflict involving good and evil. The postmodern mystery is mainly seen in the perception of religion and the recognition of good and evil in it. The latter is discussed in the article.